Synergistic Effect of Alloying on the Strength and Ductility of High Carbon Pearlitic Steel - Na Min; Yingqi Zhu; Shitao Fan; Yang Xiao; Liqin Zhou; Wei Li; Sixin Zhao (Metals, 2023)
In this work, the effects of the micro-alloying of Mn, Ni, and Si on the microstructure and mechanical properties of high-carbon pearlite steels were investigated. The results indicated that the addition of solely Ni to high-carbon pearlitic steel can enhance the strength through the refinement of interlamellar spacing, but work-hardening in the ferrite of the pearlite colony may be delayed, leading to a reduction in area. The multiple additions of Ni and the increase in Mn and Si contents in high-carbon pearlitic steel were beneficial to obtaining a balance between ultimate tensile strength and reduction in area. Three-dimensional atom probe tomography results showed Si partitioning into ferrite and Mn and Ni elements partitioning into cementite. The addition of Si inhibited the formation of a continuous network of grain-boundary cementite, leading to high strength and high ductility through optimization of the microstructure.